IgG4-related disease revealed by acute pancreatitis: A case report and literature review - Salma El Aouadi; Kaoutar Imrani; Amine Naggar; Soukaina Bahha; Nabil Moatassim Billah; Ittimade Nassar (Radiology Case Reports)
IgG4-related disease is a systemic autoimmune disorder characterized by multiorgan involvement, often presenting with pancreatic, renal, biliary, and salivary gland abnormalities. Diagnosis relies on clinical, serological, imaging, and occasionally histological findings. This report describes a 65-year-old male presenting with acute pancreatitis, bilateral renal lesions, and biliary strictures. Elevated serum IgG4 levels (3.76 g/L) confirmed the diagnosis using the 2019 ACR/EULAR and 2020 Comprehensive Diagnostic Criteria despite the lack of histological confirmation. Corticosteroid therapy led to rapid clinical and biochemical improvement, underscoring the importance of integrating multiple diagnostic modalities in managing IgG4-related disease and demonstrating the effectiveness of early intervention.